Performance analysis of thermoelectric generator implemented on non-uniform heat distribution of photovoltaic module - Mohd Ariffin, Mohd Ruzaimi; Shafie, Suhaidi; Wan Hasan, Wan Zuha; Azis, Norhafiz; Ya'acob, Mohammad Effendy; Supeni, Eris Elianddy; Wayayok, Aimrun (Elsevier, 2021)
PV–TEG hybrid system is widely discussed nowadays, as an alternative way to maximize solar radiation energy which is from both of its light and heat. In recent years, the idea of using thermoelectric generators (TEGs) to extract energy from heat waste has increased with applications varying from milliwatts to kilowatts. To form a circuit, numbers of TEG modules can be connected in series and/or parallel configuration to produce the required voltage and/or current. In the PV–TEG systems, due to operating environments, each TEG module’s power generation is subject to temperature mismatch. There is also considerable variability in the electro-thermal output and mounting pressure of each TEG module in a circuit, resulting in a significant inconsistency. Therefore, when each TEG in the array is active, a varying electrical operating point will occur at which peak energy can be obtained and problems with lower power output will occur. In this work, an individual TEG module test method was used to measure and analyze data from specific types of TEG, and a record of the maximum power output under different temperature variations is obtained. Then, the performance of the TEG system is measured and evaluated with a test bench where the modules are attached at different backside areas of generic PV panels. The non-uniform heat distribution condition created in the experiment showed an average 33 % drop in power production from the maximum power that would be available in case each TE series circuit operates under uniform heat distribution. This experimental finding demonstrates the problem and the outcomes discussed in this paper validated a thorough examination of the effect of nonuniform operating temperatures on a range of thermoelectric generator’s energy output.